2017
DOI: 10.1017/s1751731116001579
|View full text |Cite
|
Sign up to set email alerts
|

The presence of extreme feather peckers in groups of laying hens

Abstract: Feather pecking is a serious economic and welfare problem in laying hens. Feather damage occurs mainly through severe feather pecking (SFP). Selection experiments have proved that this behavior is heritable and lines have been divergently selected for high (HFP) and low feather pecking (LFP). The number of bouts of SFP per hen follows a Poisson distribution with a maximum nearby 0. A few studies indicate that the distribution within flocks is not homogenous but contains sub-groups of birds showing extremely hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The phenotypic differences between the two lines in the 15th generation can be seen in Figure 2. In Piepho et al [14], feather pecking data of the 5th to the 11th generation of both lines is shown with the same phenotypic difference over these seven generations. Hence, the two feather pecking subpopulations are both phenotypically and genotypically distinguishable, but there was little selection response in the last generations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The phenotypic differences between the two lines in the 15th generation can be seen in Figure 2. In Piepho et al [14], feather pecking data of the 5th to the 11th generation of both lines is shown with the same phenotypic difference over these seven generations. Hence, the two feather pecking subpopulations are both phenotypically and genotypically distinguishable, but there was little selection response in the last generations.…”
Section: Discussionmentioning
confidence: 78%
“…Feather pecking is not homogenous within groups of laying hens and several studies reported the presence of a subgroup of extreme feather peckers (EFP), i.e., showing an exceptional high severe feather pecking activity compared to group mates [12][13][14][15]. In a previous study [15], we detected a subgroup of extreme feather pecking hens within an F2-cross of the HFP and LFP lines mentioned above by fitting a mixture of two negative binomial distributions to feather pecking data.…”
Section: Introductionmentioning
confidence: 85%
“…Genotype: A number of studies addressed strain differences (genotypic differences) regarding feather pecking and feather pecking-related behavior [27,[37][38][39][40][41] and identified strains that have a higher propensity to develop feather pecking [29], the age of occurrence of feather pecking, and effects of selection on this behavior [35].…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we compare motor impulsivity in a line of White Leghorns selected for high FP (HFP) to that of an unselected control line (CON) to determine the contribution of the respective genetic backgrounds 27 . While we hypothesize that the HFP line exhibits higher impulsivity in general, it has long been observed that FP behaviour does not occur in all individuals in a population with this genetic predisposition 28,29 . Consequently, the motor impulsivity between phenotypic peckers (P) and non-peckers (NP) within the HFP and CON lines was also evaluated.…”
mentioning
confidence: 72%
“…This, in turn, is expected to yield valid inferences regarding the relative ranking of the different group 41 . Additionally, one can argue that selecting the highest peckers (P) in a population of HFP birds constitutes a continuation of selection 29 , as the selection of extreme phenotypes is a common breeding tool. It is also possible that the FP levels in the tested population were too low to make a significant association to motor impulsivity; however, it should be noted that FP levels are difficult to control and distinct FP groups may be formed and re-formed even after the birds are categorized into their FP groups, as the phenotypes may evolve over time 42 .…”
Section: Discussionmentioning
confidence: 99%